2013
DOI: 10.1039/c3nr33641g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–hollow PPy sphere 3D-nanoarchitecture with enhanced electrochemical performance

Abstract: A rationally designed graphene-hollow polypyrrole (PPy) nanoarchitecture in which hollow PPy spheres were inserted between graphene layers was constructed by mixing graphene oxide and polystyrene (PS)@PPy core-shell sphere, followed by reduction of graphene oxide and etching of PS. The as-prepared graphene-hollow PPy nanoarchitecture was explored as electrode material for supercapacitor applications. The specific capacitance may gradually rise to as high as 500 F g(-1) with a charging/discharging current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Figure 2f exhibits that there are almost no correlation peaks of PPy for Ni@PPy@MnO 2 and the bands from 502 cm -1 to 626 cm -1 are attributed to the Mn-O stretching vibration. [36] In addition, for Ni@MnO 2 @PPy composite, characteristic peaks at about 675 cm -1 , 935 cm -1 , 1068 cm -1 and 1085 cm -1 confirm the presence of PPy, [37] while the bands at 502 cm -1 , 626 cm -1 for MnO 2 . [36] The chemical composition and valence states of the Ni@PPy@MnO 2 and Ni@MnO 2 @PPy Meanwhile, the two weaker peaks for Mn 3+ and Mn 5+ species were also detected in the spectrum, implying that element Mn has the main chemical state of Mn 4+ .…”
Section: Chuzzle-like Ni@ppy@mno 2 Anode and Cochleate-like Ni@mno 2 mentioning
confidence: 76%
“…Figure 2f exhibits that there are almost no correlation peaks of PPy for Ni@PPy@MnO 2 and the bands from 502 cm -1 to 626 cm -1 are attributed to the Mn-O stretching vibration. [36] In addition, for Ni@MnO 2 @PPy composite, characteristic peaks at about 675 cm -1 , 935 cm -1 , 1068 cm -1 and 1085 cm -1 confirm the presence of PPy, [37] while the bands at 502 cm -1 , 626 cm -1 for MnO 2 . [36] The chemical composition and valence states of the Ni@PPy@MnO 2 and Ni@MnO 2 @PPy Meanwhile, the two weaker peaks for Mn 3+ and Mn 5+ species were also detected in the spectrum, implying that element Mn has the main chemical state of Mn 4+ .…”
Section: Chuzzle-like Ni@ppy@mno 2 Anode and Cochleate-like Ni@mno 2 mentioning
confidence: 76%
“…Hu et al also prepared ultralight graphene aerogels functionalized by ethylenediamine23. Cong et al reported a one-step fabrication of macroscopic multifunctional graphene-based hydrogels by adding ferrous ions and in situ simultaneous deposition of nanoparticles on graphene sheets, which exhibited excellent performance in the removals of pollutants28; Similar researches were carried out by other groups through modifying graphene oxide by polymers2930, metal nanoparticles610 and metal ions3132. Although progresses had been made in the preparation and application of GAs or functionalized GAs, the application of which was still restricted by their relative low mechanical strength and easy dispersion in polar solvent because of their abundant oxygen functional groups.…”
mentioning
confidence: 92%
“…[3][4][5][6][7] Supercapacitors can be sorted as pseudocapacitors and electrochemical-double-layer capacitors. Traditional materials, such as carbonbased materials, 11,12 and polymers [13][14][15] are faced with challenges of low specic capacitance (SC), inferior life cycling and mechanical degradation, which block their further development in the realm of electrode materials. Traditional materials, such as carbonbased materials, 11,12 and polymers [13][14][15] are faced with challenges of low specic capacitance (SC), inferior life cycling and mechanical degradation, which block their further development in the realm of electrode materials.…”
Section: Introductionmentioning
confidence: 99%